The association between personal social capital and health-related quality of life among Chinese older people: A cross-sectional study - Jiang, Dongdong; Yan, Yajie; Zhou, Han; Wang, Quan (Frontiers in Nutrition, 2022)
Background：Lower health-related quality of life (HRQoL) can result in adverse effects on the health of older people. This study aims to explore the relationship between personal social capital (PSC) and HRQoL among Chinese elderly people. Methods：4802 samples were included from China’s Health-Related Quality of Life Survey for Older Adults 2018. The PSC, including bonding and bridging social capital (BOC and BRC), was measured by the Chinese version of the Personal Social Capital Scale (PSCS-16). The HRQoL was evaluated by the European Five Dimensions Scale (EQ-5D-3L). Linear and Tobit regression models were conducted to examine the relationship between PSC and HRQoL. Results：The BOC and BRC of rural older people were significantly lower than those of urban older people. Pain/discomfort and anxiety/depression were the most significant health problems affecting the older samples. In the five dimensions, the proportion of rural older people with problems was higher than that of urban older people. Among rural older people, BOC was significantly related to self-rated health and EQ-5D utility index (p< 0.05); while BRC was insignificantly associated with self-rated health (p > 0.05) but related to EQ-5D utility index (p< 0.05). Both BOC and BRC were significantly correlated with self-rated health and EQ-5D utility index (p< 0.05). Conclusions：Our study reveals older people’s worrying PSC and HRQoL status. The relationship between PSC and HRQoL suggested that more social support and care of intimates should be encouraged to increase the PSC of older people, especially rural older people.